Wyprawa do krainy prawdopodobieństwa – o dokumentach animowanych Marcina Podolca - Mąka-Malatyńska, Katarzyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2017)
The article analyses two student short films by Marcin Podolec, Dokument and Olbrzym, which represent the animated documentary genre. In her analysis and interpretation of films, the author uses Annabelle Honess Roe’s methodology to research this phenomenon. She expands the definition of the animated documentary base on Roe’s work.